Konsep Relasi Sains dan Agama serta Penerapannya pada Pembelajaran di Pesantren Terpadu - Rohmatulloh Rohmatulloh; M. Tajudin Zuhri; Lalan Sahlani; Iim Ibrohim (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2021)
The relationship between science and religion in its development in the West is contradictory, giving rise to the typology of science and religion to describe the relationship. One form of typology is an integration that affects the education sector. This qualitative research aimed to describe the concept of the relation between science and religion and to describe the integrated learning system in one of the integrated boarding schools in West Java. The result of the study showed that science and religion in the view of Islam are integrated so that they cannot be separated because they are one science from Allah SWT. Regarding its application in learning in boarding school, it was found that learning did not separate between general science or science and religion in school subjects and daily activities to create students with noble character.